2023
DOI: 10.1101/2023.10.24.563814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-type-resolved somatic mosaicism reveals clonal dynamics of the human forebrain

Changuk Chung,
Xiaoxu Yang,
Robert F. Hevner
et al.

Abstract: Debate remains around anatomic origins of specific brain cell subtypes and lineage relationships within the human forebrain. Thus, direct observation in the mature human brain is critical for a complete understanding of the structural organization and cellular origins. Here, we utilize brain mosaic variation within specific cell types as distinct indicators for clonal dynamics, denoted as cell-type-specific Mosaic Variant Barcode Analysis. From four hemispheres from two different human neurotypical donors, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Tangential excitatory neuron migration was also detected, albeit related excitatory neurons were more localized than inhibitory neurons. Tangential migration is also seen with sequencing studies that find neurons with specific mutations in multiple brain regions (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 93%
“…Tangential excitatory neuron migration was also detected, albeit related excitatory neurons were more localized than inhibitory neurons. Tangential migration is also seen with sequencing studies that find neurons with specific mutations in multiple brain regions (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 93%
“…In addition to glutamatergic neurons and astrocytes, a small subset of cells from other lineages are also mutated, including GABAergic neurons and microglia. Most GABAergic neurons in the cortex originate from the ganglionic eminences, although recent studies have suggested that a portion of interneurons may have a dorsal origin [27][28][29][30] , while microglia derive from the mesoderm. This finding implies that FCDII lesions (at least the more extended ones, with high VAF) would originate from mutations that presumably occurred prior to the separation of these cell types into different lineages (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, our spatial transcriptomic data demonstrate the presence of MEIS2 + PAX6 + INs in the white matter of both the prenatal and postnatal human brain, indicating their potential role as white matter interneurons. With recent reports of a shared origin between some cortical interneurons and ENs 87,88 , it remains to be determined whether INs derived from Tri-IPCs also differentiate into cortical interneurons.…”
Section: Discussionmentioning
confidence: 99%